A Personality Study of The Main Character In Luca Movie - Ni Putu Dian Ayu Lestari; Ida Bagus Gde Nova Winarta (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2023)
Nowadays we can meet people with various types of personality that are diverse and sometimes unique. Therefore, this research entitled